Resilience and Social Support on Depression Risk for Chronic Obstructive Pulmonary Disease Patients in South Tangerang, Indonesia - Menaldi, Adhityawarman; Asih, Sali Rahadi; Mardhiyyah, Farah Ainul (Kesmas, 2026)
Chronic obstructive pulmonary disease (COPD) is a major public health concern with psychosocial impacts, such as reduced resilience and depression. This study examined the moderating role of perceived social support on the relationship between resilience and depression among individuals diagnosed with COPD in South Tangerang, Indonesia. A quantitative cross-sectional study was conducted between January and February 2024 using self-administered questionnaires. Participants were adult patients with clinically diagnosed COPD, recruited from all public health centers (PHC) in South Tangerang. A total of 125 participants met the inclusion criteria and were included in the analysis. Participants had a mean age of 41.46±15.69 years, with a balanced distribution (51.2% male, 48.8% female). Descriptive analysis showed high resilience (mean = 29.27±7.20), very high social support (mean = 70.36±14.47), and depression scores (mean = 4.65±4.59) below the cutoff. Moderation regression analysis using Hayes’ PROCESS Model 1 showed that resilience, with perceived social support as a moderator, explained 18% of the variance in depression scores (R² = 0.1807). These findings emphasized the importance of integrating psychosocial factors into COPD management. Strengthening resilience and social support within PHC settings may enhance mental health outcomes among COPD patients.